2014
DOI: 10.1007/s11239-014-1063-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of homocysteine-thiolactone on plasma fibrin networks

Abstract: Epidemiologic studies have shown that hyperhomocysteinemia is an independent risk factor for vascular disease. Homocysteine (Hcy) circulates as different species, mostly protein bound, and approximately 1% as its reduced form and the cyclic thioester homocysteine-thiolactone (HTL). Despite the level of plasma thiolactone being markedly low, detrimental effects are related to its high reactivity. HTL reacts with proteins by acylation of free basic amino groups; in particular, the epsilon-amino group of lysine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…HHCY has been related to impaired formation of the fibrin network [ 36 , 37 ]. HCY impairs the fibrinolysis networks by inducing slower coagulation process and rendering more tightly packed fibrin clots [ 10 ].Under the influence of HCY, fibrin networks resulted in a more compact structure with shorter, thicker and more branched fibers, these structural properties of fibrin are related to slower spontaneous lysis rate of thrombus, and proved to be less permeable and more resistant to fibrinolysis [ 38 , 39 ]. Moreover, studies have revealed that mild HHCY (>10umol/L) showed markedly relationship with decreased tissue-type plasminogen activator (t-PA) activity (which is the major activator of fibrinolysis) and impaired spontaneous thrombolysis in STEMI patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HHCY has been related to impaired formation of the fibrin network [ 36 , 37 ]. HCY impairs the fibrinolysis networks by inducing slower coagulation process and rendering more tightly packed fibrin clots [ 10 ].Under the influence of HCY, fibrin networks resulted in a more compact structure with shorter, thicker and more branched fibers, these structural properties of fibrin are related to slower spontaneous lysis rate of thrombus, and proved to be less permeable and more resistant to fibrinolysis [ 38 , 39 ]. Moreover, studies have revealed that mild HHCY (>10umol/L) showed markedly relationship with decreased tissue-type plasminogen activator (t-PA) activity (which is the major activator of fibrinolysis) and impaired spontaneous thrombolysis in STEMI patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine (HCY) is a sulfur-containing amino acid that functions as a key intermediate in methionine metabolism [ 8 ], which is believed to promote atherothrombosis through several mechanism [ 9 ], and hyperhomocystenemia (HHCY) (plasma HCY > 10 mmol/L) is currently recognized as a new independent risk factor for atherosclerotic vascualr disease. Furthermore, HHCY is related to impaired formation of the fibrin networkby inducing slower coagulation process and rendering more tightly packed fibrin clots, hence influencing the process of spontaneous thrombolysis [ 10 ]. Therefore, we speculated that HCY might be a predictor of early SR in STEMI patients.…”
Section: Introductionmentioning
confidence: 99%
“…The slower lysis is caused by impaired activation of plasminogen on N-Hcy-fibrin (273). Confocal microscopy of N-Hcy-fibrin clots reveals a denser structure with increased branching, relative to unmodified fibrin (75,182), which can explain why lysis of N-Hcy-fibrin is slower than control fibrin. N-Hcy-fibrinogen has the ability to form disulfide-linked complexes with albumin; this, however, has no effect on lysis of N-Hcy-fibrin clots (274).…”
Section: N-hcy-fibrinogenmentioning
confidence: 99%
“…HTL reacts with proteins by acylation of free basic amino groups. In particular, the epsilon-amino group of lysine residues forms adducts and induces structural and functional changes in plasma proteins [ 3 ]. High levels of homocysteine impair endothelial function and cause endothelial damage in humans and in animal models [ 4 , 5 ], indicating that the endothelial monolayer is very sensitive to changes in plasma homocysteine levels.…”
Section: Introductionmentioning
confidence: 99%